(3OjhGf GdCYTis - (3CHhHUjQ ejehf Hf bjS Hf LfOd GdhGFdi CYTi bjSs; (3GdJdYaQj , eMeO Hf jhSa Hf eSYhO GdTjHGfj, TgGH GdOjf CHh YHO Gddg,J (B675 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI(B: (3cJGH ajg ef pCTYGQ GdCYTi bGd GdCYTi, hGSeg hgh CMO Hfj bjS Hf KYdHI hCbHd YfO XghQ GdfHj UdYe MJi CJi ecI s
(3BNQgG (B:s
(3ef bUjOI bGdgG aj jhe Pj bGQ(B: (3hbGJdhG Gdbhe Ef GdbJd ecQeI EPG Jdhi Hca GdeYUe GdYRa Ke TYQ GdCYTi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3cJHJ ddCejf eMeO Hf GdEeGe GdefUhQ HGddg Hf CejQ GdeDefjf YHOGddg Hf MeRI Hf SdjeGfs
(3hHBNQgG bQGAI hELGRI ddCejQ LeGd GdOjf Ydj Hf eMeO GdfGUQ dOjf Gddg Ydi hGdOgs
(3heDQNI aj TgQ QeVGf SfI (B645(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B25s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B29 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B776s
Keywords: (3GdCOHs